Patofisiologi Patent Ductus Arteriosus - Kino; Hariyanto, Didik; Perdana, Rully; Byant, Nadhila Annisa (Fakultas Kedokteran, Universitas Andalas, 2025)
Background: Patent ductus arteriosus (PDA) is a congenital heart defect resulting from the failure of the ductus arteriosus to close after birth. This condition leads to a left-to-right shunt between the aorta and the pulmonary artery, which may cause increased pulmonary blood flow, pulmonary hypertension, and heart failure if left untreated. Physiological closure of the ductus arteriosus after birth depends on postnatal circulatory changes and the regulation of molecular mediators, particularly prostaglandin E2 and nitric oxide, with additional contributions from genetic factors. Objective: To describe the role of molecular mechanisms and genetic factors in the pathophysiology of PDA and to highlight their implications for diagnostic and therapeutic approaches. Methods: This article is based on a narrative review of the scientific literature addressing the pathophysiology of PDA, with particular emphasis on the roles of prostaglandins, nitric oxide, and genetic factors such as the TBX1 gene and the Notch signaling pathway. Results: The literature indicates that persistent prostaglandin E2 levels and ongoing nitric oxide activity contribute to the maintenance of ductal patency after birth, especially in preterm neonates. Moreover, dysregulation of the TBX1 gene and alterations in the Notch signaling pathway are associated with impaired development and reduced contractility of ductus arteriosus smooth muscle, thereby hindering normal physiological closure. These findings provide a mechanistic basis for the use of prostaglandin-inhibiting pharmacological therapy in the management of PDA. Conclusion: Patent ductus arteriosus is a multifactorial condition driven by complex interactions between molecular mediators and genetic determinants. A comprehensive understanding of these mechanisms is essential for optimizing PDA management through more precise, pathophysiology-based therapeutic strategies.